Finishing properties of shellac by using different viscosity and abrasive paper applied on sepetir (sindora spp.) / Atikah Ab Hamid - Ab Hamid, Atikah (Faculty of Applied Sciences, 2015)
Finishing is the last process in furniture manufacturing and it is importance in determined the quality of a furniture. In this study, the finishing properties of shellac by using different viscosity and abrasive paper were ascertained. Two type of viscosity that has been chosen were 7cP and 11cP. Then, silicon carbide and aluminum oxide which used number grit 180 and 220 were the two types of sandpaper used. Three types of finishing testing were applied to all samples which were cross-cut test, household test and cigarette test. This study is based on two types of standard testing which was ASTM and BS standard. For tis study, it shows that there is no significant different in the finishing properties when different type of viscosity and sandpaper applied. In household test, the quality of both set of samples was same. Meanwhile for cross-cut test, the quality of finishing with viscosity 11cP was better than 7cP. This is because viscosity 11cP is more concentrated than viscosity 7cP. Over all, Sepetir has better finishing quality when applied with 11 cP viscosity of shellac with aluminum oxide.